sole for x: - 3x - 5 < 10

Question

Asked 3/21/2012 12:08:56 PM

Updated 7/16/2014 3:01:48 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [7/16/2014 2:58:13 AM]

s

btatkerson|Points 1108|

ambrosio_09|Points 1040|

debnjerry|Points 28615|

debnjerry|Points 28615|

Question

Asked 3/21/2012 12:08:56 PM

Updated 7/16/2014 3:01:48 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [7/16/2014 2:58:13 AM]

Rating

3

- 3x - 5 < 10

- 3x < 10 + 5

- 3x < 15

x > -5

- 3x < 10 + 5

- 3x < 15

x > -5

Added 7/16/2014 2:57:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:02:42 AM]

3

(x + 5) (x - 3) = x^2 - 3x + 5x - 15 = x^2 + 2x - 15

Added 7/16/2014 2:58:54 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:02:55 AM]

3

12x^2y +18xy^2 + 6x = 6x(2xy + 3y^2 + 1)

Added 7/16/2014 3:00:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:21 AM]

3

-9x^0 = -9

Added 7/16/2014 3:00:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:34 AM]

3

(x^2 + 2x -4) - (x^2 - 5x + 2)

= x^2 + 2x -4 - x^2 + 5x - 2

= 7x - 6

= x^2 + 2x -4 - x^2 + 5x - 2

= 7x - 6

Added 7/16/2014 3:01:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:03:51 AM]

Solve by using PEMDAS: 4 + 3^2 / (6-4) User: solve by using PEMDAS: 8 x 2 +9 /3 **Weegy:** 6 x 3 + 10 ? 2 = 18+5 = 23 **User:** simplify: 6(y + 7) **Weegy:** 42y is the answer **User:** Multiply: (5xy^4) (2x^2y) **Weegy:** Do you have more to the equation? **User:** solve for x: -4x + 7 = 35 **Weegy:** The answer is x=-6,2. [ x^(2)-12=-4x
Since -4x contains the variable to solve for, move it to the left-hand side of the equation by adding 4x to both sides.
x^(2)-12+4x=0
Reorder the polynomial x^(2)-12+4x alphabetically from left to right, starting with the highest order term.
x^(2)+4x-12=0
In this problem 6*-2=-12 and 6-2=4, so insert 6 as the right hand term of one factor and -2 as the right-hand term of the other factor.
(x+6)(x-2)=0
Set each of the factors of the left-hand side of the equation equal to 0.
x+6=0_x-2=0
Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.
x=-6_x-2=0
Set each of the factors of the left-hand side of the equation equal to 0.
x=-6_x-2=0
Since -2 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 2 to both sides.
x=-6_x=2
The complete solution is the set of the individual solutions.
x=-6,2 ] **User:** solve for x: 4(x - 3) = 5(2x + 3) **Weegy:** 2x - 6 + 5x = 10x + 30 combine like terms
7x - 6 = 10x + 30 subtract 7x and 30 both sides
-36 = 3x divide both sides by 3
-12 = x
Checking :
[ 2(x-3)+5x=5(2x+6)
2((-12)-3)+5(-12)=5(2(-12)+6)
2(-15) + 5(-12) = 5(-24+6)
-30 - 60 = 5(-18)
-90 = -90 - - - > true
therefore, x = -12
] **User:** degree of the polynomial **Weegy:** An example of a polynomial is 2x5 ? 5x3 ? 10x + 9. **User:** given the polynomial x^5 + x^3 - 5x^9 + 6x^2. what is the degree of the polynomial ? **User:** evaluate; x^2 + 13x + 15 when x= **User:** x^0 is equal to o **Weegy:** The answer is zero. The property is ... (More)

Question

Updated 6/28/2014 2:56:14 PM

6 Answers/Comments

8 x 2 +9 /3

= 16 + 3 = 19

= 16 + 3 = 19

Added 6/28/2014 2:51:11 PM

This answer has been confirmed as correct and helpful.

(5xy^4) (2x^2y) = 10x^3y^5

Added 6/28/2014 2:51:47 PM

This answer has been confirmed as correct and helpful.

4(x - 3) = 5(2x + 3);

4x - 12 = 10x + 15;

4x - 10x = 15 + 12;

-6x = 27;

x = -27/6 = -9/2

4x - 12 = 10x + 15;

4x - 10x = 15 + 12;

-6x = 27;

x = -27/6 = -9/2

Added 6/28/2014 2:53:13 PM

This answer has been confirmed as correct and helpful.

The degree of polynomial x^5 + x^3 - 5x^9 + 6x^2 is 9.

Added 6/28/2014 2:54:08 PM

This answer has been confirmed as correct and helpful.

x^0 is NOT equal to 0.

Anything that is raised to 0 is always equal to 1.

Anything that is raised to 0 is always equal to 1.

Added 6/28/2014 2:56:14 PM

This answer has been confirmed as correct and helpful.

31,220,164

questions answered

denyang

$172.20

Hearts 3,966 Views 967,245 Streams 470

phpmicro

$169.30

Hearts 3,573 Views 732,513 Streams 263

wildflower14344

$163.15

Hearts 3,627 Views 1,388,600 Streams 513

emdjay23

$152.05

Hearts 3,108 Views 646,428 Streams 229

maydj

$141.25

Hearts 3,364 Views 750,363 Streams 325

Flora1988

$113.90

Hearts 2,523 Views 354,030 Streams 172

miyaka

$110.00

Hearts 2,507 Views 458,982 Streams 326

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

There are no comments.